Public health nutrition principles and practice in community and global health - Stein, Natalie (Jones & Bartlett Learning, 2015)
"This book is a comprehensive introduction to Public Health Nutrition, andhas a unique balance, focusing on the health of communities and nations, and presenting the most significant public health nutrition problems and solutions worldwide"--Provided by publisher.